2003
DOI: 10.1248/bpb.26.579
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of Mouse Mevalonate Pyrophosphate Decarboxylase

Abstract: Mevalonate pyrophosphate decarboxylase (MPD) is considered to be a cytosolic protein. Recently, other groups reported that MPD is mostly located in the peroxisomes. In this study, we examined whether the expression of MPD in mice depends on the proliferation of peroxisomes, and whether MPD is predominantly located in the peroxisomes or the cytosol of mice. No increase in the protein level of MPD was observed in the crude extract of the livers of mice administered with peroxisome proliferative drugs. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…We previously reported that MPD is predominantly located in the cytosol of B16F10 without melanin; 13) however, no subcellular distribution of MPD in B16 containing a lot of melanin was found. In order to identify whether the subcellular distribution of MPD changed by differences in melanin biosynthesis, the subcellular distribution of MPD in B16 was examined using permeabilized cells, which retain their organelle integrity yet lack cytosolic components.…”
Section: Selective Permeabilization Of the Plasma Membrane And Releamentioning
confidence: 80%
See 1 more Smart Citation
“…We previously reported that MPD is predominantly located in the cytosol of B16F10 without melanin; 13) however, no subcellular distribution of MPD in B16 containing a lot of melanin was found. In order to identify whether the subcellular distribution of MPD changed by differences in melanin biosynthesis, the subcellular distribution of MPD in B16 was examined using permeabilized cells, which retain their organelle integrity yet lack cytosolic components.…”
Section: Selective Permeabilization Of the Plasma Membrane And Releamentioning
confidence: 80%
“…8) We previously reported that MPD was predominantly located in the cytosol of rat hepatocytes, 12) normal rat kidney cells (NRK), 12) or mouse melanoma cells (B16F10) 13) treated with fetal bovine serum (FBS), respectively, since in permeabilized rat hepatocytes, NRK, or B16F10 treated with digitonin, which lack cytosolic enzymes, MPD was mainly present in the medium (cytosolic fraction).…”
Section: Introductionmentioning
confidence: 99%
“…Cell Fractionation Isolation of post-nuclear supernatant (PNS), mitochondria, peroxisome, lysosome (MPL), and microsomal and cytosol fractions from various guinea pig tissues by cell fractionation was carried out as described by Michihara et al 14) Tissues were homogenized with 3 volumes of homogenate buffer without Triton X-100. The homogenate was centrifuged at 1000ϫg for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is little information on the gene expression of MPD in rats, although analyses of the MPD protein have been performed. [6][7][8][9][10][11][12][13] Thus, we examined the distribution of the mRNA levels in Wistar rat tissues by real-time PCR, to clarify the relationship between protein and mRNA levels of MPD. Next, we compared the mRNA levels of MPD in liver and brain between SHRSP and normotensive WKY.…”
Section: Introductionmentioning
confidence: 99%